Peraturan di Tingkat Desa Legal? - Antari, Putu Eva Ditayani; Utama, I Made Arya (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
Villages are stated to be the smallest government structure in Indonesia. A village is an area that has certain boundaries, as a legal community unit that has the right to regulate and manage the affairs of local communities based on their origins. Apart from that, the village government also has the authority to determine legislative products mentioned in village regulations. However, this form of legal regulation is not included in the hierarchy of legal regulations in Indonesia, and in practice it is rarely known by the public. Therefore, this research will focus on identifying the legality of the position of regulations in villages as part of the national legal and regulatory framework. The research method used is a normative legal research method which discusses the position and legality of regulations in the village based on applicable laws and regulations as primary legal material. Apart from that, the discussion is also complemented by secondary legal materials in the form of books and articles published in journals based on theories, concepts, as well as legal principles and adages. The research results show that the village government is the smallest unit in the government system in Indonesia. The village government, like other governments in the region, has the authority to regulate and manage its government affairs autonomously based on the division of affairs and rights according to the origins of the village. Regarding this authority, the village government has the authority to form village regulations and village head regulations. The status and legitimacy of village regulations and village head regulations are recognized as statutory regulations and have binding legal force as long as they are formed based on higher statutory regulations or based on their authority over the village's original rights.